A new species of the leafhopper genus Riseveinus Li, 1995 (Hemiptera: Cicadellidae: Evacanthinae) from China - Li, Yu-Jian; Li, Zi-Zhong (Zootaxa, 2012)
The paper deals with the species of the Oriental leafhopper genus Riseveinus Li. A new species, R. baoshanensis sp. nov., from Yunnan Province, China is described and a key to species is provided.